2016
DOI: 10.1002/iid3.118
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-sensing liver X receptors stimulate Th2-driven allergic eosinophilic asthma in mice

Abstract: IntroductionLiver X receptors (LXRs) are nuclear receptors that function as cholesterol sensors and regulate cholesterol homeostasis. High cholesterol has been recognized as a risk factor in asthma; however, the mechanism of this linkage is not known.MethodsTo explore the importance of cholesterol homeostasis for asthma, we investigated the contribution of LXR activity in an ovalbumin‐ and a house dust mite‐driven eosinophilic asthma mouse model.ResultsIn both models, airway inflammation, airway hyper‐reactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Liver X receptors are other important nuclear receptors that function as cholesterol sensors and regulate cholesterol homeostasis (28). A primary function of LXRα as a cholesterol sensor is to maintain cellular cholesterol homeostasis by participating in the process of reverse cholesterol transport (29). LXRα can regulate the expression of genes involved in reverse cholesterol transport, such as ABCA1 and ABCG1, which mediate cholesterol efflux to lipid-poor apolipoproteins (30).…”
Section: Discussionmentioning
confidence: 99%
“…Liver X receptors are other important nuclear receptors that function as cholesterol sensors and regulate cholesterol homeostasis (28). A primary function of LXRα as a cholesterol sensor is to maintain cellular cholesterol homeostasis by participating in the process of reverse cholesterol transport (29). LXRα can regulate the expression of genes involved in reverse cholesterol transport, such as ABCA1 and ABCG1, which mediate cholesterol efflux to lipid-poor apolipoproteins (30).…”
Section: Discussionmentioning
confidence: 99%
“…In an ovalbumin model of asthma in BALB/C mice, GW3965 was reported to worsen airway hyperresponsiveness without affecting inflammation (Birrell, et al, 2008). By contrast, another group has shown that LXR-null mice from a different genetic background have reduced eosinophilic inflammation, mucus, and airway hyperresponsiveness in both the ovalbumin and house dust mite models of asthma, whereas GW3965 aggravates eosinophilia (Smet, et al, 2016).…”
Section: Lxr Agonists In Preclinical Models Of Inflammatory Diseasementioning
confidence: 98%
“…Metabolites of the MA pathway, particularly the isoprenoids, have been associated with processes linked to asthma and respiratory ailments, including allergic eosinophilic inflammation [31,36,69], Rho GTPase signaling in airway smooth muscle cells and airway hyperreactivity (AHR) [48,70,71], adaptive immunity and type 2 inflammation [72,73], airway smooth muscle cell proliferation [43], and mucus production [74] (Figure 2). Since these pathogenic mechanisms occur in asthma, perturbation of the MA pathway likely affects disease pathogenesis [29,70].…”
Section: The Mevalonate Pathway Statins and Relevance To Asthmamentioning
confidence: 99%